Queen-queen competition and reproductive skew in a cardiocondyla ant - Hashim, Rosli; Heinze, J.; Yamauchi, K.; Ishida, Y. (2007)
Queens and female sexuals of the Southeast Asian ant Cardiocondyla sp. engage in aggressive interactions. By biting and violently antennating female sexuals, queens appear to prevent them from shedding their wings and presumably also from starting to lay haploid eggs. Aggression among dealate queens apparently results in the establishment of reproductive rank orders with considerable differences in offspring production among individual nestmate queens, as visualized by the pronounced color polymorphism of this taxon. Reproductive skew ranged from complete monopolization of both worker and female sexual production to more or less equal partitioning of reproduction. Division of reproduction was associated with variation in the location of queens close to or away from the center of the brood pile, which again appeared to be caused by queen-queen antagonism.